Chilean Public Policies and Their Impact on Biotechnology Small and Medium Enterprises - Torres-Zapata, I (Universitat de Barcelona, Facultad de Economia y Empresa, 2022)
It is difficult to find cases of technology-based Small and Medium Enterprises in developing countries, however Chile has some within the biotechnology sector. How has this been possible? As a consequence of the different public policies and structural economic conditions that allowed their emergence, especially in the 1990s. This study describes the historical conditions and how they have been able to create a sector within the Chilean economy. From the analysis of secondary data the emergence of this type of company within the country is described. This analysis shows the link between structural conditions and appropriate public policies, meaning that these companies did not emerge by chance. Understanding their development process is crucial to promote the creation of more such technology-based Small and Medium Enterprises, as they have many positive externalities and are more globally competitive. © 2022, Universitat de Barcelona, Facultad de Economia y Empresa. All rights reserved.